2022
DOI: 10.4103/jcrt.jcrt_1183_21
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating duct cell carcinoma in lactating adenoma: A rare case in pair

Abstract: Lactating adenomas, though considered being benign, sometimes turn out to be malignant. We are hereby presenting two cases of lactating adenomas which turned out to be harboring infiltrating duct cell carcinoma (DCC). Two lactating women with mass in the breast were referred from surgery for fine-needle aspiration cytology and biopsy. On histopathology, it was found that both had infiltrating DCC (either as collision tumor or as a malignant transformation of lactating adenoma). These cases point toward some as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…3 To the best of our knowledge, only 7 cases of concurrent lactating adenoma and invasive breast carcinoma have been reported in current English literature, with our case being the eighth. [4][5][6][7][8][9] The underlying pathogenesis for its coexistence remains unclear. The popular opinion is lactating adenomas are benign entities and their coexistence with invasive carcinoma is a mere collision tumor, however, few consider it to have malignant potential.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 To the best of our knowledge, only 7 cases of concurrent lactating adenoma and invasive breast carcinoma have been reported in current English literature, with our case being the eighth. [4][5][6][7][8][9] The underlying pathogenesis for its coexistence remains unclear. The popular opinion is lactating adenomas are benign entities and their coexistence with invasive carcinoma is a mere collision tumor, however, few consider it to have malignant potential.…”
Section: Discussionmentioning
confidence: 99%
“…On microscopic examination, half the cases had distinct areas of malignant and benign lesions supporting the theory of collision, and one case showing intermingling of the two cell populations suggesting infiltration. However, Kumar et al 6 and Dakhure et al 7 reported carcinoma in situ admixed with LA, and Sharma et al 9 reported carcinoma in the center of LA suggesting a malignant potential of LA. The present case had IBC adjacent to LA, with a distinctly demarcated boundary separated by an area of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation